A logging service as a universal subscriber - Sharp, Jessica (Kansas State University, 2014)
As medical systems expand to allow for the increase the number of devices, new ways to protect patient safety have be developed. The Integrated Clinical Environment, ICE, standard sets up a set of standards that define what an integrated hospital system is. Within the specification is a direct call for a forensic logger that can be used to review patient and system data. The MDCF is one implementation of the ICE standard, but it lacked a key component the ICE standard requires, a logger. Many loggers exist in industry, with varying rates of success and usefulness. A medically sound logger has to be able to completely retell exactly what happened during an event, including patient, device, and system information, so that the right medical professional can provide the best care. Several loggers have been built for MDCF, but few were practical due to the invasiveness of the service. A universal subscriber, a service that is able to connect to all publishing data streams, logging service was built for the MDCF which has the ability to record all information that passes over the MDCF messaging service. This implementation was then stress tested with varying numbers of devices and amounts of data. A reviewing tool was also built that allows for replay of device data that is similar to the original device UI. Future work will include looking into storing system information such as state changes within MDCF and system health. There is also a push to further integrate the forensic reviewer into the core MDCF UI.
Keywords: Medical Device Coordination Framework; Universal subscriber; Logger; Computer Science (0984)